Characterization of MdpS: an in-depth analysis of a MUC5B-degrading protease from Streptococcus oralis - Leo, Fredrik; Lood, Rolf; Thomsson, Kristina A.; Nilsson, Jonas; Svensäter, Gunnel; Wickström, Claes (Frontiers in Microbiology, 2024)
Oral biofilms, comprising hundreds of bacteria and other microorganisms on oral mucosal and dental surfaces, play a central role in oral health and disease dynamics. Streptococcus oralis, a key constituent of these biofilms, contributes significantly to the formation of which, serving as an early colonizer and microcolony scaffold. The interaction between S. oralis and the orally predominant mucin, MUC5B, is pivotal in biofilm development, yet the mechanism underlying MUC5B degradation remains poorly understood. This study introduces MdpS (Mucin Degrading Protease from Streptococcus oralis), a protease that extensively hydrolyses MUC5B and offers an insight into its evolutionary conservation, physicochemical properties, and substrate-and amino acid specificity. MdpS exhibits high sequence conservation within the species and also explicitly among early biofilm colonizing streptococci. It is a calcium or magnesium dependent serine protease with strict physicochemical preferences, including narrow pH and temperature tolerance, and high sensitivity to increasing concentrations of sodium chloride and reducing agents. Furthermore, MdpS primarily hydrolyzes proteins with O-glycans, but also shows activity towards immunoglobulins IgA1/2 and IgM, suggesting potential immunomodulatory effects. Significantly, MdpS extensively degrades MUC5B in the N-and C-terminal domains, emphasizing its role in mucin degradation, with implications for carbon and nitrogen sequestration for S. oralis or oral biofilm cross-feeding. Moreover, depending on substrate glycosylation, the amino acids serine, threonine or cysteine triggers the enzymatic action. Understanding the interplay between S. oralis and MUC5B, facilitated by MdpS, has significant implications for the management of a healthy eubiotic oral microenvironment, offering potential targets for interventions aimed at modulating oral biofilm composition and succession. Additionally, since MdpS does not rely on O-glycan removal prior to extensive peptide backbone hydrolysis, the MdpS data challenges the current model of MUC5B degradation. These findings emphasize the necessity for further research in this field.